Consumers' preferences on the Swiss car market: A revealed preference approach. (March 2019) - Weber, Sylvain
Abstract: This paper investigates demand responses to variations in the characteristics of the vehicles. Our investigation is based on number of sales for each model marketed over the period 2006–2015 in Switzerland, and puts particular emphasis on fuel efficiency, curb weight, horsepower, and the potential interactions between these attributes. We find that market shares are significantly higher for more efficient and powerful vehicles, while light cars are preferred to heavy ones. Our results also point to a gradual increase of sensitivity to fuel efficiency over the last decade. However, interaction effects between engine fuel efficiency and power indicate a lower marginal valuation of fuel efficiency in the market segments for relatively powerful cars, hence a lower sensitivity to fuel efficiency among the consumers with the highest potential for polluting emissions. Also, these findings point to potential rebound effects, where consumers give up part of the expected fuel savings by purchasing more powerful vehicles. Highlights: The Swiss car market is investigated using a combined dataset of technical characteristics and sales figures. Market shares increase with fuel efficiency and horsepower, while light cars are preferred to heavy ones. Sensitivity to fuel efficiency is low among the consumers with the highest potential for polluting emissions. Possible rebound effects exist, whereby improved fuel efficiency leads consumers to purchase more powerful vehicles.